Associated factors and profile of injuries in professional ballroom dancers in Brazil: A cross-sectional study - Cardoso A.A. (2020)
© 2020 Universidade Estadual Paulista - UNESP. All rights reserved.Aims: Ballroom dance consists of a modality characterized by fast and dynamic movements performed in pairs, aiming at technical and artistic excellence. Objective: To analyze the prevalence, characteristics, and factors associated with injuries in professional ballroom dancers, considering possible differences between sexes. Method: 320 professional dancers of both sexes with a mean age of 31.48â?}8.63 years, who were in professional companies and/or dance schools from five regions of Brazil. The measurement was performed through an online self-administered questionnaire about general information and injuries. Results: A high frequency of musculoskeletal injuries (80.0%) was observed, especially osteoarticular ones (52.4%). In women, the lower limbs were the anatomical location most reported (31.1%) and the knee in male dancers (28.7%). Overweight men, with more than 11 years of dance practice, who danced in companies and also performed other physical activities, were more likely to have injuries. However, women were less likely to have injuries when they were overweight and more likely when they practiced other dance modalities besides ballroom dancing. Conclusions: Approximately 64.1% of ballroom dancers suffered an injury throughout their professional careers. For men, being overweight as well as the search for complementary activities to the physical training routine for both sexes, seem to influence the occurrence of injuries. Identification of the factors associated with injuries in ballroom dancers contributes both to preventive actions and to rehabilitation processes, favoring a healthy and safe career for professionals involved in this practice.